2018
DOI: 10.1177/0954008318779429
|View full text |Cite
|
Sign up to set email alerts
|

High thermally stable thermosetting polyimides derived from a carborane-containing tetramine

Abstract: In this study, we report the preparation of thermosetting polyimides (PIs) based on carborane-containing tetramine and their characterizations. The novel tetramine 1,2-bis(4-(3,5-diaminobenzoic acid phenyl ester))carborane (CBNH) was synthesized and characterized firstly. Then, it was used in the preparation of two kinds of branched imide oligomers via the method of thermal imidization. The cure behavior of the obtained phenylethynyl-terminated oligomers was investigated by differential scanning calorimetry. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…34 After thermal-oxidative aging, the composite had a T g of 252°C and a T gmod of 215°C, both increased by the higher aging temperature of 190°C, which may accelerate the physical aging and postcure rate of the material. 35 The tan δ peak for the thermal-oxidative aged composite can be accordingly observed in Figure 4(b) to shift toward a higher temperature. 31 This indicates that the T800 carbon fiber–epoxy composite material evaluated in this study has good resistance to aging.…”
Section: Resultsmentioning
confidence: 89%
“…34 After thermal-oxidative aging, the composite had a T g of 252°C and a T gmod of 215°C, both increased by the higher aging temperature of 190°C, which may accelerate the physical aging and postcure rate of the material. 35 The tan δ peak for the thermal-oxidative aged composite can be accordingly observed in Figure 4(b) to shift toward a higher temperature. 31 This indicates that the T800 carbon fiber–epoxy composite material evaluated in this study has good resistance to aging.…”
Section: Resultsmentioning
confidence: 89%
“…21 The DSC results indicated that the novel method had some effect on the heat resistance of resulting polyimide but would not significantly reduce the glass transition temperature. The results suggested that the obtained polyimide has excellent thermal properties, which were similar to the thermosetting polyimides 19 and the quaternary copolymerized thermoplastic polyimide. Obviously, the resulting polyimide was stable up to 400 C and did not present conspicuous mass loss before this temperature.…”
Section: Thermal Analysismentioning
confidence: 64%
“…19,20 Thermal stability of the resulting polyimide is necessary to be studied to verify the influence of hydrothermal method on their thermal properties. 19,20 Thermal stability of the resulting polyimide is necessary to be studied to verify the influence of hydrothermal method on their thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…This may be because the post-curing process of the resin increases the cross-linking density, decreases the free volume of the polymer, decreases the activity of the molecular chains, and decreases the average chain length between adjacent cross-linking points; the physical aging and post-curing reactions may cause the material T g to rise. 38,39 However, long-term thermal–oxidative aging may cause degradation of the resin and destruction of the molecular structure, resulting in a decrease in the T g . 40 The T g of the material after aging for 1920 h still exceeds that of the unaged composite, indicating that the resin has good heat-resistant oxidative aging properties.…”
Section: Resultsmentioning
confidence: 99%